ULASAN : ANALISIS VARIAN BAGI PENGUKURAN BERULANG - Suaib, Suaib (Jurnal Agroteknos, 2011)
ABSTRACT A variety of methods are available for analysing repeated measurements data where the outcome is continuous. However, there is little information on how established methods is compared in practice with methods that have become available to applied statisticians more recently, and multilevel models. The aim of this paper was to exemplify the use of this method, and directly compare the results by the application of a hypothetical data set. The focus was on practical aspects rather than technical issues. The data considered were taken from a livestock trial of treatments for pasture in 20 chows, in which a baseline and four post-randomization measurements of outcomes were taken. The simplicity of the method of summary statistics using the post-randomization mean of observations provided a useful initial analysis.Key words: Analysis of variance, repeated measures, applying in broad aspects